The Essentials of Power System Dynamics and Control - Pota, Hemanshu Roy (Springer Singapore, 2018)
This book presents a general framework for modelling power system devices to develop complete electromechanical models for synchronous machines, induction machines, and power electronic devices. It also presents linear system analysis tools that are specific to power systems and which are not generally taught in undergraduate linear system courses. Lastly, the book covers the application of the models, analysis and tools to the design of automatic voltage controllers and power system stabilisers, both for single-machine-infinite-bus systems and multi-machine interconnected systems. In most textbooks modelling, dynamic analysis, and control are closely linked to the computation methods used for analysis and design. In contrast, this book separates the essential principles and the computational methods used for power system dynamics and control. The clear distinction between principles and methods makes the potentially daunting task of designing controllers for power systems much easier to approach. A rich set of exercises is also included, and represents an integral part of the book. Students can immediately apply-using any computational tool or software-the essential principles discussed here to practical problems, helping them master the essentials.